Occupational accidents in hyperbaric-chambers inside attendants in France - Pougnet, Richard; Henckes, Anne; Pougnet, Laurence; Cochard, Guy; Dantec, Françoise; Dewitte, Jean-Dominique; Loddé, Brice (La Medicina del Lavoro, 2015)
Introduction: The purpose of the study was to assess the number of accidents among staff employed in the operation of hyperbaric chambers in France. Materials and Methods: A retrospective study using a questionnaire was carried out on occupational accidents in France between 2005 and 2011. Results: 12 (46%) centres participated in the study, representing 73 subjects. The mean age was 43.5 years (SD=9.73). They had worked in hyperbaric chambers for 9.8 years on average (SD=7.7). The average number of hyperbaric sessions was 198.3 per subject (SD=174.25), for a total of 8.072 hyperbaric sessions; 27% of the subjects reported that they had at least one accident during the study period. In all, 30 accidents were reported: 3 blood exposures, 4 accidents related to patient handling, 20 hyperbaric accidents; 3 other accidents. Of the hyperbaric accidents, 2 (10%) involved decompression sicknesses with cutaneous symptoms, 3 (15%) decompression illness (DCI), 14 (70%) ear traumatisms, 1 (5%) dental accident. The incidences were 372 per 100,000 sessions in hyperbaric chambers (SHC) for all accidents, 248 per 100,000 SHC for hyperbaric accidents and 173 per 100,000 SHC for ENT barotraumas. Conclusion: The accidents involving staff operating hyperbaric chambers were mainly ear traumatisms..